NEGATIVE CONSEQUENCES OF FOREIN DIRECT INVESTMENTS - Experiences from different countries- - Vujović, Slavoljub; Stevanović, Simo; Petrović, Dragana (Economics of Agriculture, 2010)
According to theories on direct foreign investments and examples in practise, and using directions from normative and historic method, in this paper are analysed negative consequences of foreign direct investments on economies of different countries, with emphasis on agriculture. There are many support to foreign direct investments (FDI) from the government, as the only salutary solution for slacken economy, in countries like Serbia, Croatia, Macedonia, Albania, etc. Real positions of economies (in Poland, Hungary, Mexico, Egypt, Croatia, Serbia, Costa Rica, Brazil, Bolivia, Chile, etc), where FDI were welcomed as the only salutary solution, recommended from IMF and WB, by title "structural adjustment", "macroeconomic stability and competitiveness" for economy and government of these countries, reveal the true face of FDI. According to Goldsmith E., Mender J., 1996, ruthless search for lowest wage, softest provisions (often on the edge of the law) and the cheapest resources in the aim of achieving extra profit, are often called "race to the bottom", where "employees and government race for job with other workers and other countries, and competition is based on following: Who will work for less money? Who will accept half time job? Who will abandon social insurance and provisions regarding protection on working place? Who will allow that toxic waste is thrown in his back yard?"